Quiet Corruption: Anti-Corruption's Trojan Horse - Samuel Harrison-Cudjoe (Centre for Behaviour and Wellness Advocacy, 2018)
Globally, the concept of corruption has taken different shades over the years. Due to this trend, may forms of corrupt acts have silently been perpetuated in Ghana. This paper seeks to provide insights into 'quite corruption' and how it affects development and standards of living. It also suggests some measures to combat this menace.